Analisis Kemampuan Berpikir Kritis Berimplementasi Children Learning In Science Berbantuan Media Kotak Belajar Ajaib pada Murid Sekolah Dasar - Halimah, Siti Musyarofah Nur; Fajrie, Nur; Fathurohman, Irfai (Universitas Muria Kudus, 2024)
This research have purpose to describe critical thinking abilities fifth grade students at SD N Ngajaran Rembang through the implementation CLIS learning model with help KOBELA media. Researchers used mixed research methods with Sequential Explanatory approach. The research subjects consisted of thirty-two class V students at SDN Ngajaran Rembang. The instruments used include questionnaires, interviews, student responses, and written tests. The results research show teachers tend conduct lectures they do not utilize existing learning methods and media, especially in science content, material is seeing through light, hearing through sound. Teachers have not innovated using learning media increases students' ability think critically. This makes students less interested in conventional media which material for seeing because light and hearing because of sound. It can concluded fifth grade students at SDN Ngajaran need innovative learning models and media strengthen teaching and learning process of seeing, light, hearing and sound support the learning process.